Physical education 4 team sports : basketball and volleyball - Del Rosario, Jhomel E.; Del Rosario, Leo S.; Padrid, Daniel Xerxes S. (Malabon City : Mutya Publishing House, 2023)
"Ball sports provide students with opportunities to acquire knowledge of strategies, appreciation, and develop skills in team sports, and maintain and/or improve their personal fitness. The content includes knowledge and application skills, techniques, strategies, rules and safety practices in basketball and volleyball. This course analyses some team sports from an educational and practical dimension. For this, it uses two principles: methodological aspects and the essence of each sport. This subject tries to discover methodological tools that allow us to consider sport not only as something competitive and technical but also as an essential component for training of person, social cohesion and skills acquisition for health."
Includes appendices and references.
English.
Keywords: Physical education--Sports